Construction of Islam in Two Versions of Nyai Dasima by G. Francis and S.M. Ardan - Ashari, Dwi; Putra, Ahmad Al Amin; Karim, M. Ilham Nurul; Priyansyah, Hafiz (Southeast Asian Language and Literature Studies, 2024)
There are many versions of Nyai Dasima, two of them were written by G. Francis and S.M. Ardan. In these versions, there are numerous binaries that can be examined in greater depth, including identity, culture, and Islamic beliefs. These two versions describe the early days of Islam in Indonesia using distinct methods and levels. It is undeniable that the writing of G. Francis, who is western-based, colonial, and liberal, is inaccurate or at the very least skewed in describing the Islamic teachings that are placed in a number of crucial situations in the Nyai Dasima plot. In the version by G. Francis, there are numerous inappropriate dictions, such as the use of the term kafir (infidel) and numerous flaws in the written story when describing Islamic teachings. On the other hand, S.M. Ardan wrote Nyai Dasima’s version by illustrating the good and evil concepts of Islamic teachings according to the context of the time, such as the devout Muslims attending the langgar (musalla) for prayer, the thriving practice of polygamy, and the use of witchcraft for love affairs. Both versions of Nyai Dasima criticize the construction of Islam in distinct ways, so neither is superior. The Nyai Dasima version of S.M. Ardan complements the distancing G. Francis interpretation. Nyai Dasima presents a distinct perspective on Islam in each version. Not to mention, these two versions also explain the differences in the way they present of the plot, which more prominently depict the various faces of Islam.